Efficacy of Intravenous Immunoglobulin/Exchange Transfusion Therapy on Gestational Alloimmune Liver Disease - Yeh, Pai-Jui; Huang, Shiu-Feng; Chiang, Ming-Chou; Wang, Chao-Jan; Lai, Ming-Wei (Frontiers in Pediatrics, 2021)
Background Gestational alloimmune liver disease (GALD) is a rare but critical cause of neonatal liver failure. After discovering the maternal-fetal alloimmune mechanism, intravenous immunoglobulin (IVIG) with or without exchange transfusion (ET) has gradually replaced antioxidant cocktails as the first line therapy. Whether such therapy changes the outcome of neonates with GALD is yet to be defined. Method We reported a pair of twins with discordant presentations, mild and self-limited in the older, whereas liver failure in the younger, who was successfully rescued by ET and IVIG. To investigate the outcome after therapeutic alteration, 39 cases between 2005 and 2020 from a literature research were collected. Results Half of the collected cases (47.1%) were preterm. Common presentations were ascites, jaundice, respiratory distress, hepatomegaly, and edema. Leading laboratory abnormalities were coagulopathy, hypoalbuminemia, and elevated serum ferritin. Salivary gland biopsy and magnetic resonance imaging detected extrahepatic siderosis in 70% (14/20) and 56% (14/25), respectively. IVIG, ET and liver transplantation were performed in 19 (48.7%), 15 (38.5%), and 8 (20.5%) patients, respectively. The overall survival (OS) rate and native liver survival (NLS) rate were 64.1% (25/39) and 43.6% (17/39). Although the compiled results did not support a significant benefit, the OS and NLS were higher in the IVIG with/without ET group compared with those treated with conventional therapy [OS (70% vs. 57.9%) and NLS (55% vs. 31.6%), respectively]. Conclusion A high index of suspicion for GALD is crucial when facing a neonate with liver failure. Despite no significant influence on the outcome over conventional therapy in such a rare and detrimental disease, IVIG with or without ET can be worth trying before resorting to liver transplantation, which is resource-demanding and technique-challenging in small infants.